PENGARUH MODEL BRALANCING BERBANTUAN WORDWALL TERHADAP LITERASI DIGITAL IPAS SISWA KELAS IV SD DI GUGUS VIII KECAMATAN BULELENG - Rina Andayani, Komang; Putu Candra Prastya Dewi, Ni; Arya Wiradnyana, I Gede (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the effect of the Balancing learning model assisted by Wordwall media on the digital literacy of fourth-grade students in science at elementary school Gugus VIII, Buleleng District. This study used a quantitative approach with a quasi-experimental type and a nonequivalent control group design. The study population was all fourth-grade students in elementary school Gugus VIII, Buleleng District, with a purposive sampling technique. Data were collected through a digital literacy observation sheet instrument, then analyzed using descriptive and inferential statistical analysis which included prerequisite tests (normality and homogeneity tests) and hypothesis testing (t-test). The results showed that there was a significant effect of the use of the Balancing model assisted by Wordwall media on students' digital literacy. This was indicated by the achievement of digital literacy indicators in the experimental class which was more optimal compared to the control class. The Balancing model plays a role in balancing student learning activities, especially in the Brain Balance Quiz phase through the integration of interactive Wordwall media. The use of this media can increase student engagement and make it easier for teachers to monitor aspects of digital culture contextually. Thus, the Balancing model assisted by Wordwall media is effectively used as an alternative learning innovation to improve students' digital literacy in science at elementary schools.